Investigation On Compressed Stabilized Earth Block Using Laterite Soil Stabilized with Cement - Thamendaran, Magindran (2018)
An increase towards urban development have created less importance towards rural areas as the community depending on economical and low cost housing. This study is based on determining geotechnical properties of laterite soil encountered in Sungai Buloh. Related journals and articles were reviewed to obtain sufficient experimental result informations. The objectives of this study were satisfied by a series of preliminary laboratory experiments. Comparison from past researchers were made for each experiments to justify and assure the results obtained are diverse and favourable. The main aim of this study is to obtain unconfined compressive strength, UCS of suitable natural geotechnical properties of laterite soil stabilized with cement in the production of CSEB. The findings from this research started with Natural Moisture Content, NMC of laterite soil ranged at 17.04%. Particle size distribution curve shows that the soil is well graded with proportions of aggregate less than 15%, sand and fine grains in the range more than 50%. Liquid Limit, Plastic Limit and Plasticity Index of laterite soil is 40.13%, 26.53% and 13.60% respectively. Plasticity Chart plot lies above A-line classifying as soil containing inorganic clays of low or medium plasticity (CL). Laterite soil attains Optimum moisture content, OMC at 16% and Maximum dry density, MDD at 1.88